Diagnosis of brain death by transcranial Doppler sonography. Issue 12 (December 1988) - Bode, H; Sauer, M; Pringsheim, W
Abstract : The blood flow velocities in the basal cerebral arteries can be recorded at any age by transcranial Doppler sonography. We examined nine children with either initial or developing clinical signs of brain death. Soon after successful resuscitation increased diastolic flow velocities indicated a probable decrease in cerebrovascular resistance; this was of no particular prognostic importance. As soon as there was a clinical deterioration, there was a reduction in flow velocities with retrograde flow during early diastole, probably due to an increase in cerebrovascular resistance; this indicated a doubtful prognosis. In eight of the nine children with clinical signs of brain death a typical reverberating flow pattern was found, which was characterised by a counterbalancing short forward flow in systole and a short retrograde flow in early diastole. This indicated arrest of cerebral blood flow. One newborn showed normal systolic and end diastolic flow velocities in the basal cerebral arteries for two days despite clinical and electroencephalographic signs of brain death. Shunting of blood through the circle of Willis without effective cerebral perfusion may explain this phenomenon. No patient had the typical reverberating flow pattern without being clinically brain dead. Transcranial Doppler sonography is a reliable technique, which can be used at the bedside for the confirmation or the exclusion of brain death in children in addition to the clinical examination.